Pseudomonas boanensis sp. nov., a bacterium isolated from river water used for household purposes in Boane District, Mozambique. Issue 7 (12th July 2022) - Nicklasson, Matilda; Martín-Rodríguez, Alberto J.; Thorell, Kaisa; Higdon, Shawn M.; Neves, Luis; Mussagy, Aidate; Rydberg, Hanna A.; Hernroth, Bodil; Svensson-Stadler, Liselott; Sjöling, Åsa
Abstract : A Gram-negative rod with a single polar flagellum was isolated from a freshwater reservoir used for household purposes in Boane District, near Maputo, Mozambique, and designated as strain DB1 T . Growth was observed at 30–42 °C (optimum, 30–37 °C) and with 0.5–1.5 % NaCl. Whole-genome-, rpoD- and 16S rRNA-based phylogenies revealed this isolate to be distant from other Pseudomonas species with Pseudomonas resinovorans, Pseudomonas furukawaii and Pseudomonas lalkuanensis being the closest relatives. Phenotypic analyses of strain DB1 T showed marked differences with respect to type strains P. resinovorans CCUG 2473 T, P. lalkuanensis CCUG 73691 T, P. furukawaii CCUG 75672 T and Pseudomonas otiditis CCUG 55592 T . Taken together, our results indicate that strain DB1 T is a representative of a novel species within the genus Pseudomonas for which the name Pseudomonas boanensis is proposed. The type strain is DB1 T (=CCUG 62977 T =CECT 30359 T ).